Public interest in the energy transition: Exploring the shift to two-wheeled electric transportation for sustainable development - Sara, Innes Gianticha; Pratama, Sandi Nur (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: Energy plays a vital role in global efforts to transition toward renewable energy sources, addressing climate change and ensuring sustainability. Despite growing investments in renewable energy, fossil fuels remain a critical commodity, particularly in Indonesia’s transportation sector, where their dominance significantly contributes to air pollution. The urgency to shift from fossil fuels to renewable energy has been heightened by geopolitical events such as Russia's aggression, which has underscored the need for energy resilience. Indonesia has initiated fiscal and non-fiscal incentives to promote the adoption of electric vehicles (EVs) as an environmentally friendly alternative. Methods: This research adopts a qualitative approach, conducting interviews with two respondents: one who owns an electric two-wheeler and another who does not. The study focuses on key factors influencing societal behavior and interest in transitioning to EVs, including price, infrastructure, brand, mobility needs, and environmental awareness. Government policies such as subsidies and tax incentives are also analyzed for their role in encouraging EV adoption. Findings: The interviews reveal that price affordability, infrastructure availability, and government subsidies significantly influence the decision to transition to electric vehicles. While environmental awareness is a contributing factor, practical considerations such as mobility needs and vehicle brand preferences remain critical. The study highlights the importance of government support in the form of improved infrastructure, subsidy programs, and standardized battery regulations to accelerate the adoption of two-wheeler EVs. Conclusion: The findings emphasize the need for targeted government policies to strengthen EV adoption, particularly through subsidies, infrastructure development, and regulatory improvements. These efforts are essential for achieving clean and sustainable energy in Indonesia. Novelty/Originality of this article: This study provides a comprehensive perspective on the socio-economic and policy-related factors influencing EV adoption in Indonesia. By incorporating first-hand insights from users and non-users of electric vehicles, it offers unique recommendations to enhance the transition toward renewable energy.